Reconstruction of Marriage and Divorce Law for Civil Servants - Lakoni, Lakoni; Ardiansyah, M.; Juwita, Masayu Nila (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article analyzes Government Regulation Number 45 of 1990, this regulation contains gaps in polygamy arrangements between men and women who are civil servants. The focus of this article is to describe the construction of polygamy regulations for the State Civil Apparatus (ASN) which seems gender biased, then how efforts to reconstruct polygamy rules for the State Civil Apparatus (ASN) and then analyze its contribution to the reform of Islamic family law in Indonesia. This library research article is descriptive analytical. The primary data sources in writing this article are the Qur'an, Hadith, and positive laws in Indonesia that regulate marriage and divorce for Civil Servants. The analysis uses the theory of Mashlahah Mursalah, Gender and Feminist Amina Wadud and Gustav Redbruch's theory of legal objectives. The result of the analysis is Government Regulation Number 45 of 1990 concerning Marriage and Divorce Permits for Civil Servants which regulates polygamy for Civil Servants, must be rejected because it contains legal content that is not fair to women as legal subjects. It should be reconstructed by providing equitable regulations, no discrimination, and equalizing the position of men and women before the law. Keyword: Reconstruction, Marriage and Divorce Law, Civil Servants